Combined nucleobase and backbone modifications enhance DNA duplex stability and preserve biocompatibility - El-Sagheer, A; Brown, T (Royal Society of Chemistry, 2014)
DNA strands containing a triazole linkage flanked on its 3′-side by an aminoethylphenoxazine nucleobase analogue (G-clamp) have been prepared by solid-phase synthesis followed by CuAAC-mediated click oligonucleotide ligation. The stability of the doubly modified DNA duplexes and DNA-RNA hybrids is greatly increased, whereas a single base pair mismatch located at or adjacent to the modifications is strongly destabilising, making triazole G-clamp a potent mismatch/point mutation sensor. A DNA strand containing this unnatural combination was successfully amplified by PCR to produce unmodified copies of the original template, with deoxyguanosine inserted opposite to the G-clamp-triazole nucleotide analogue. This study shows for the first time that a polymerase enzyme can read through a combined backbone/nucleobase modification surprisingly well. These favourable properties suggest new applications for oligonucleotides containing the G-clamp triazole modification in biotechnology, nanotechnology, diagnostics and therapeutics. © 2013 The Royal Society of Chemistry.